Epistemiation: An Approach for Knowledge Elicitation of Expert Users During Product Design. (September 2016) - Boring, Ronald L.; Lew, Roger; Ulrich, Thomas A.
The Guideline for Operational Nuclear Usability and Knowledge Elicitation (GONUKE) outlines multiple types and stages of human factors evaluation to support system design activities. Originally developed to support human factors requirements for control room modernization at nuclear power plants, GONUKE includes verification, validation, and epistemiation. Epistemiation is a novel term for the process in which knowledge from expert users is elicited to shape the design of the system. Especially in the case of control rooms, the importance of knowledge transfer between expert operators and system designers may prove more beneficial than traditional verification and validation. This paper outlines epistemiation, provides background on expert users, and illustrates the process through a case study. Although GONUKE and epistemiation are native to nuclear power applications, the approach is generalizable to other domains that feature expert users.